2007
DOI: 10.1577/m06-038.1
|View full text |Cite
|
Sign up to set email alerts
|

Population Characteristics of Shovelnose Sturgeon in the Upper Wabash River, Indiana

Abstract: Shovelnose sturgeon Scaphirhynchus platorynchus support a commercial fishery throughout much of the Mississippi and Missouri River drainages. There is concern that harvest closures for Eurasian sturgeons (Acipenseridae) may result in increased exploitation of shovelnose sturgeon to meet global demands for caviar. Population attributes of shovelnose sturgeon were examined in the upper Wabash River, Indiana, from April 2003 through November 2004 between Wabash and Terre Haute. Fish (N ¼ 4,849) were captured by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
3
18
2
Order By: Relevance
“…In our study, FL frequency distributions, age estimates, and length-atage data were within the range of other similar studies (Figure 1; Morrow et al 1998;Kennedy et al 2007), suggesting a potential lack of aging error. As for other assumptions associated with catch-at-age models, constant recruitment is rarely observed in fish stocks (Maceina and Pereira 2007;Miranda and Bettoli 2007;Phelps et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, FL frequency distributions, age estimates, and length-atage data were within the range of other similar studies (Figure 1; Morrow et al 1998;Kennedy et al 2007), suggesting a potential lack of aging error. As for other assumptions associated with catch-at-age models, constant recruitment is rarely observed in fish stocks (Maceina and Pereira 2007;Miranda and Bettoli 2007;Phelps et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…1). The drainage area is approximately 85 500 km 2 (Kennedy, Daugherty, Sutton & Fisher 2007). The upper section of the Wabash River (upstream of Lafayette‐West Lafayette, Indiana) is characterised by shallow (0.3–3 m) water depths and sand, gravel, cobble and bedrock substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Interpreting age and growth from calcified structures assumes that annuli are formed at a constant frequency and the distance between annuli is proportional to a fish's somatic growth (Campana and Neilson 1985). However, the accuracy of age estimates obtained from such structures is rarely successfully validated (i.e., absolute age; Campana 2001), and several authors have reported use with caution especially with shovelnose sturgeon (Scaphirhynchus platorynchus) (Whiteman et al 2004;Jackson et al 2007;Kennedy et al 2007;Killgore et al 2007). Recent work by Hamel et al (2014) concluded that the assumptions of consistent annuli deposition and proportionality of annuli spacing to fish somatic growth are violated for pallid sturgeon (Scaphirhynchus albus).…”
Section: Introductionmentioning
confidence: 99%